A Multi-commodity Network Flow Model for Sustainable Performance Evaluation in City Logistics: Application to the Distribution of Multi-tenant Buildings in Tokyo - Dupas, Rémy; Taniguchi, Eiichi; Deschamps, Jean-Christophe; Qureshi, Ali G. (Sustainability, 2020)
The distribution of goods in crowded city centers is a major challenge. In this paper, we propose a methodology for evaluating the performance of a parcel distribution network in city logistics. This methodology encompasses the main entities of a two-tier distribution system made up of carriers, huge shopping centers (multi-tenant buildings) and intermediate depots (urban consolidation centers), as well as the parcel flows between them. This methodology aims to optimize the transport flows (distance traveled) of a given distribution network while also quantifying the impact in terms of sustainable development by measuring gas emissions. Two different states of the network with different connectivity degrees are evaluated and compared: the current state of the network as well as its future state. The transport network modeling is based on a network flow, which is expressed in linear programming and implemented with an optimization solver. The validation of this methodology is based on the parcel distribution of the Multi-tenant Buildings of the city of Tokyo. The findings are that the network with greater connectivity between the entities brings significant traveled distance reduction as well as a reduction of emissions of CO2. Another finding is that the grouping of the parcels (i.e., pooling) brings a reduction of the distance traveled compared to the transport organization without grouping and contributes to a reduction in the number of trucks.